ANALISIS KECEPATAN WAKTU TEMPUH PERJALANAN KENDARAAN PERTAMINA KHUSUS SPBU KOTA SAMARINDA - HEUMASSE SANAKY, HANCE (KURVA S JURNAL MAHASISWA, 2014)
One of the main couses of trafic acidents are noncomplociace motorists wich include driving at heviy speed regartdless of trafic signs indicating motor vhecile speed limit. this study discuses and evaluates the road caharateristic and speed of road user especialy motor vechlies and the performance of the speed limite signes of Martadinata street, and the preception of road users for non-compliance with the signs in place. the method used is direct field surveys such as trafic survey. the survey speed with local metal using a Gps (Global Positioning Syestem) SPSS 18.0 and a survey speed the care pertamina Spbu kota samarinda. survey are trafic and using a quistionere the results show that the total flow (Q) is 2,297 Pcu/Hour in Martadinata Street flow velocity (Fv) Is 22.91 Km/Hour road segment capacity (C) is 13,783 Smp/Hour and the degree of saturation is 0,33 furtermore. it is shown that many violations of the speed limit signes occur in street Mr.Martadinata Road Segmen.Keywood Speed Limit,Trafice,Acidents,Trafic Viola